The Effects of Spillway Width on Outflow Discharge and Flow Elevation for the Probable Maximum Flood (PMF) - Yeri Sutopo; Karuniadi Satrio Utomo; Naufal Tinov (Salehan Institute of Higher Education, 2022)
The purpose of this study was to analyze the effect of spillway width on flow elevation at the weir crest based on the flood discharge design for the Probable Maximum Flood (PMF) return period using flood routing hydrologically at the Cacaban Dam (Indonesia). The rainfall Probable Maximum Precipitation (PMP) design uses the Hershfield Equation. The design of the flood discharge analysis of QPMF used the Nakayasu Synthetic Unit Hydrograph (HSS). Flood routing uses the hydrologic routing method. The Cacaban Dam is located in Jati Village, Kedung Banteng District, Tegal Regency, Central Java Province, Indonesia. The results of the research data analysis showed that increased spillway crest widths led to decreased flow evaluation at the spillway crest, and increased outflow discharge. Thus, if a large storage volume of the reservoir is intended, then the width of the spillway crest must be reduced. Otherwise, the width of the spillway crest must be increased. In terms of flood control in the Tegal Regency, it's better to make the crest of the spillway smaller. Doi: 10.28991/CEJ-2022-08-04-08 Full Text: PDF